2015
DOI: 10.1175/jamc-d-14-0009.1
|View full text |Cite
|
Sign up to set email alerts
|

A Surface Wind Extremes (“Wind Lulls” and “Wind Blows”) Climatology for Central North America and Adjoining Oceans (1979–2012)

Abstract: This study explores long-term deviations from wind averages, specifically near the surface across central North America and adjoining oceans (258-508N, 608-1308W) for 1979-2012 (408 months) by utilizing the North American Regional Reanalysis 10-m wind climate datasets. Regions where periods of anomalous wind speeds were observed (i.e., 1 standard deviation below/above both the long-term mean annual and mean monthly wind speeds at each grid point) were identified. These two climatic extremes were classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Ruiz- Barradas and Nigam, 2006;Radic and Clarke, 2011). At the same time, embedded forecast models can be used within the framework of the Coordinated Regional Climate Downscaling Experiment (CORDEX; Martynov et al, 2013) within a seamless framework for weather and climate prediction, whereby model deficiencies that differ in spatial scales and timescales can be more readily understood (Brown et al, 2012). They also offer useful datasets for designing new infrastructure, particularly if they are sufficiently long and spatially relevant to define the likelihood of extremes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruiz- Barradas and Nigam, 2006;Radic and Clarke, 2011). At the same time, embedded forecast models can be used within the framework of the Coordinated Regional Climate Downscaling Experiment (CORDEX; Martynov et al, 2013) within a seamless framework for weather and climate prediction, whereby model deficiencies that differ in spatial scales and timescales can be more readily understood (Brown et al, 2012). They also offer useful datasets for designing new infrastructure, particularly if they are sufficiently long and spatially relevant to define the likelihood of extremes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the COSMO (Consortium for Small-scale Modelling) 6 km reanalysis has shown the potential to provide realistic sub-daily representations of winds at 10 to 40 m of height (Borsche et al, 2016) and to resolve small-scale cloud structures (Bollmeyer et al, 2015). NARR was used to define a climatology of surface wind extremes (Malloy et al, 2015) and 30-year trends in wind at hub height (Holt and Wang, 2012) over northern America.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed a slowdown in terrestrial SWS at many regions (Bichet et al, ; Tobin et al, ; Berrisford et al, ). In North America, the slowdown in SWS was mainly found in Canada and America (Pryor et al, ; Pryor and Ledolter, ; Greene et al, ; Malloy et al, ). The reduction in SWS also found in Europe, including France (Najac et al, ), Czech Republic (Brazdil et al, ), Netherlands (Cusack, ), Switzerland (McVicar et al, ), Turkey (Dadaser‐Celik and Cengiz, ), Spain, and Portugal (Azorin‐Molina et al, ; ).…”
Section: Introductionmentioning
confidence: 99%
“…Ruiz-Barradas and Nigam, 2006;Radic and Clarke, 2011). At the same time, embedded forecast models can be used within the framework of the Coordinated Regional Climate Downscaling Experiment (CORDEX; Martynov et al, 2013) within a seamless framework for weather and climate prediction, whereby model deficiencies that differ in spatial scales and timescales can be more readily understood (Brown et al, 2012). They also offer useful datasets for designing new infrastructure, particularly if they are sufficiently long and spatially relevant to define the likelihood of extremes.…”
Section: Introductionmentioning
confidence: 99%